Esophageal cancer and bacterial part of gut microbiota – A multidisciplinary point of view - Muszyński, Damian; Kudra, Anna; Sobocki, Bartosz Kamil; Folwarski, Marcin; Vitale, Ermanno; Filetti, Veronica; Dudzic, Wojciech; Kaźmierczak-Siedlecka, Karolina; Połom, Karol (Frontiers in Cellular and Infection Microbiology, 2022)
There is an urgent need to search for new screening methods that allow early detection of esophageal cancer and thus achieve better clinical outcomes. Nowadays, it is known that the esophagus is not a sterile part of the gastrointestinal tract. It is colonized with various microorganisms therefore a “healthy” esophageal microbiome exists. The dysbiotic changes of esophageal microbiome can lead to the development of esophageal diseases including esophageal cancer. There is a strong consensus in the literature that the intestinal microbiome may be involved in esophageal carcinogenesis. Recently, emphasis has also been placed on the relationship between the oral microbiome and the occurrence of esophageal cancer. According to recent studies, some of the bacteria present in the oral cavity, such as Tannerella forsythia, Streptococcus anginosus, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Fusobacterium nucleatum may contribute to the development of this cancer. Moreover, the oral microbiome of patients with esophageal cancer differs significantly from that of healthy individuals. This opens new insights into the search for a microbiome-associated marker for early identification of patients at high risk for developing this cancer.